Efeito da luz de LED branca, vermelha, azul e verde em parâmetros da fisiologia da cianobactéria Aphanocapsa holsatica: taxa de crescimento, produção de biomoléculas e biofixação do CO₂ - Lima, Amanda Ellen Viana (2022)
Cyanobacteria is unicellular prokaryotic group of microrganisms that is receiving attention as a commercial producer of biomolecules through the ability to biofix CO₂. This match in ecology and industry is being encouraged by companies and governments to reduce the impacts of global warming. Highlighting even more these photosynthetic organisms with industrial application and their commercialized biomolecules, such as proteins, biomass and pigments. Thus, the identification of new strains with biotechnological potential and their physiological elucidation are very important . To identify cultivation conditions that are favorable to produce biomolecule concomitantly with high rates of CO₂ biofixation is important for the implementation of such ecological initiatives. The use of different colors of light modifies photosynthesis and, consequently, the metabolism. Therefore, it can be applied as a strategy to increase microorganisms growth rate and the accumulation of biomolecules. This work aimed to analyze the effects of red, green, blue and white lights on photosynthesis, biomolecule production and population growth of the cyanobacterium Aphanocapsa holsatica (CCIBt 3053). In a physiological perspective, we analyzed the total concentration of proteins, carbohydrates, lipids and pigments (chlorophyll a, total carotenoids and phycocyanin). In addition, we monitored photosynthesis parameters using the Phyto-PAM II equipment. The results showed that white light is the best for biomass accumulation, with 287.11 ± 17.13 mg/L at the end of the experiment (96 h). Green light induced a 3-fold increase in protein concentration per dry biomass (63.78%), in addition to increasing the concentration of chlorophyll a without reducing the carotenoids concentration. Blue light cells culture was identified with the highest electron transfer rates as well as the highest effective photosynthetic yield. Furthermore, we conclude lower energy lights improved health parameters of A. holsatica (CCIBt 3053) by increasing the photosynthetic yield and protein concentration. The strain did not show chromatic acclimatization. This research is a contribution to the physiology of a cyanobacteria that can be applied to biotechnology related to photosynthesizing prokaryotic organisms.